Thermal performance assessment of phase change material integrated cementitious composites in buildings: Experimental and numerical approach. (1st December 2017) - Ramakrishnan, Sayanthan; Wang, Xiaoming; Sanjayan, Jay; Wilson, John
Highlights: New kind of PCM integrated cementitious composite (PCMCB) was developed and characterized. Prototype experiments showed PCMCB significantly reduced indoor temperature fluctuations. Thermal performance of PCMCB in buildings was assessed with numerical simulations. Night ventilation is required to maximize the cold storage of PCM. Abstract: This paper presents a comprehensive experimental and numerical investigation on thermal enhancement of form-stable phase change material (PCM) integrated cementitious composites, with the goal of applying as interior surface plastering mortars in building walls. The composite PCM fabricated on paraffin/hydrophobic expanded perlite (EPO) showed an apparent density and 28-day compressive strength of 1244.2 kg/m 3 and 17.9 MPa respectively, when integrated into ordinary cementitious composite at 80% volume replacement of fine aggregate. The thermal performance of PCM integrated cementitious composites was experimentally assessed using a prototype test cell made with PCM integrated cement boards (PCMCB) subjected to realistic temperature cycles. The comparison study considers two reference prototypes made with gypsum plasterboards (GPB) and ordinary cement boards (OCB). It was found that the prototype incorporated with PCMCB reduced the peak indoor temperature by up to 2.8 °C and 4.43 °C during typical summer days and summer design days respectively, compared to the GPB test cell. Numerical simulations conducted on a multi-storey office building for the application of PCMCB as interior surface plastering mortars showed that the PCMCB could significantly reduce the peak indoor temperature and diurnal temperature fluctuations. Indeed, the interior surface application of PCM has limited cold storage at night, leading to reduced latent heat storage. However, cold storage of PCM could be improved by introducing night ventilation. The combined application of PCMCB and night ventilation reduced the peak indoor operative temperature by up to 3.4 °C, as opposed to 2.5 °C for building refurbishment with PCMCB only.